2014
DOI: 10.1177/1457496914557015
|View full text |Cite
|
Sign up to set email alerts
|

Operative Treatment of Primary Hyperparathyroidism in Daycare Surgery

Abstract: Objective: the standard of care for primary hyperparathyroidism is surgical removal of hyperfunctional parathyroid tissue. Here, we describe 20 patients with primary hyperparathyroidism who were treated surgically in the setting of daycare surgery.Design: prospective observational study.Methods: a total of 20 patients with primary hyperparathyroidism were operated between march 2005 and may 2010. the follow-up period had a median of 41 weeks (5-245 weeks). results are presented as mean (± standard deviation) o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…At study inclusion and at discharge after thyroidectomy, patients were counseled about hypocalcemic symptoms. Increased awareness and focus on physical sensations may have caused the higher number of patients seeking medical care ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…At study inclusion and at discharge after thyroidectomy, patients were counseled about hypocalcemic symptoms. Increased awareness and focus on physical sensations may have caused the higher number of patients seeking medical care ( 34 ).…”
Section: Discussionmentioning
confidence: 99%
“…11 12 Several studies have demonstrated that same-day discharge after parathyroidectomy is feasible with low rates of postoperative complications. 3 4 5 6 7 8 10 13 14 15 16 Importantly, these reports acknowledge that accelerated discharge pathways are not appropriate for all patients undergoing parathyroidectomy.…”
Section: Discussionmentioning
confidence: 99%
“… 2 3 Despite these concerns, several studies from high-volume, academic centers have demonstrated that parathyroidectomy can be safely performed with discharge on the day of surgery or on the 1 st postoperative day. 3 4 5 6 7 8 9 10 The purpose of the present study was to report the results of parathyroidectomy at a 'medium-volume' endocrine unit in a District General Hospital setting before and after the implementation of a protocol intended to reduce the postoperative length of stay (LOS) by focusing on periprocedural patient education and postoperative management of calcium monitoring and supplementation.…”
Section: Introductionmentioning
confidence: 99%
“…It should be hoped to identify selection strategies of the patients that need some specific exams or tools in the perspective of curtailing unnecessary charges. In our specific field, we are convinced that the hospital stay could be reduced at only one overnight in a number of cases, given that the management in one-day surgery and even in day-care surgery have been proposed (34)(35)(36); moreover, we could select the use of the ioPTH and start to perform some MIVAP procedures under local anaesthesia with the aim of reducing the specific charges of the general anaesthesia. These measures could increase the number of cases which cost are under the standard value of the reimbursement.…”
Section: Discussionmentioning
confidence: 99%